Biodegradation of low concentration of monochloroacetic acid-degrading Bacillus sp. TW1 isolated from Terengganu water treatment and distribution plant - Zulkifly, Ahmad Hafiz; Roslan, D.D; Hamid, A. A. A; Hamdan, Sallehuddin (Asian Network for Scientific Information, 2010)
Haloacetic acids (HAAs) are group of chemicals formed due to disinfection by products that can be detected during chlorination and chloramination of processed drinking water. In this study, Bacillus sp. strain TW1 identified by morphological/biochemical and PCR-amplified 16S rRNA gene was isolated from Kuala Terengganu water treatment and distribution plant. TW1 was isolated due to its ability to grow in low concentration of monochloroacetic acid (MCA) of 0.5 mM, 10 times lower than normal MCA as sole carbon and energy source. Bacterial cell culture was grown in liquid minimal medium, pH 6.5 at 30°C on rotary shaker (150 rpm). Degradation of monochloroacetic acid was detected by measuring the amount of chloride ion released in the liquid minimal medium. Strain TW1 degraded monochloroacetic acid at best with maximum chloride ion released of 0.32 μmol Cl mL-1 using 0.5 mM MCA concentration. Current results demonstrated that this is the first reported study on low concentration of MCA degradation by Bacillus sp. TW1.